2015
DOI: 10.3390/molecules20046443
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hepatoprotective Effect of Penthorum chinense Pursh Extract against t-BHP-Induced Liver Damage in L02 Cells

Abstract: Penthorum chinense Pursh (P. chinense), a traditional Chinese medicine used by the Chinese Miao minority, has been used to treat liver diseases for a long time. However, the mechanism behind the liver protective effects of P. chinense remains unclear so far. The aim of the present study was to investigate the hepatoprotective effect of P. chinense and its possible mechanism(s). Immortalized normal human normal liver L02 cells were used to evaluate the protective effect of P. chinense aqueous extract against te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Nevertheless, in modern biological science, there have been only a few reports concerning this useful plant. Some studies have reported on antioxidant and anti-cancer cancer properties of P. chinensis, as well as on potential hepatoprotective, antiviral and anti-diabetic uses (Cao et al 2015;Hu et al 2015;Huang et al 2015;Lu et al 2012;Wang et al 2015;Zhang et al 2013). Certain bioactive compounds including quercitrin, quercetin-3-O-rhamnoside, gallic acid, β-sitosterol, thonningianins A, 5-hydroxy-flavanone-7-Obeta-D-glucoside, 2,4,6-trihydroxybenzoic acid, pinocembrin-7-O-beta-glucoside, 5-methoxy-pinocembrin-7-O-β-D-glucoside and pinocembrin-7-O-[3''-O-galloyl-4'',6''-hexahydroxydiphenoyl]-beta-glucose have been isolated from this plant species (Feng et al 2001;Lu et al 2012;Wang et al 2006Wang et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in modern biological science, there have been only a few reports concerning this useful plant. Some studies have reported on antioxidant and anti-cancer cancer properties of P. chinensis, as well as on potential hepatoprotective, antiviral and anti-diabetic uses (Cao et al 2015;Hu et al 2015;Huang et al 2015;Lu et al 2012;Wang et al 2015;Zhang et al 2013). Certain bioactive compounds including quercitrin, quercetin-3-O-rhamnoside, gallic acid, β-sitosterol, thonningianins A, 5-hydroxy-flavanone-7-Obeta-D-glucoside, 2,4,6-trihydroxybenzoic acid, pinocembrin-7-O-beta-glucoside, 5-methoxy-pinocembrin-7-O-β-D-glucoside and pinocembrin-7-O-[3''-O-galloyl-4'',6''-hexahydroxydiphenoyl]-beta-glucose have been isolated from this plant species (Feng et al 2001;Lu et al 2012;Wang et al 2006Wang et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Although a certain ROS level is essential for cellular survival, cellular death may occur when oxidative stress caused by ROS production, exceeds the cellular antioxidant abilities [14,15]. An excessive ROS production has been reported to cause DNA damage, modify proteins and lipid functions, and activate the related signal pathways [15].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive oxidative stress is reported to be associated with a variety of diseases [14]. Although a certain ROS level is essential for cellular survival, cellular death may occur when oxidative stress caused by ROS production, exceeds the cellular antioxidant abilities [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the cellular antioxidant defense system counterbalances ROS production to maintain an appropriate balance between oxidants and antioxidants (4). Therefore, antioxidant therapy may be one strategy to prevent cells from excessive exposure to oxidative stress and correct cellular redox homeostasis (5).…”
Section: Introductionmentioning
confidence: 99%